2021
DOI: 10.1089/bfm.2020.0312
|View full text |Cite
|
Sign up to set email alerts
|

Black/African American Breastfeeding Experience: Cultural, Sociological, and Health Dimensions Through an Equity Lens

Abstract: Background: Disparities in breastfeeding (BF) continue to be a public health challenge, as currently only 42% of infants in the world and 25.6% of infants in the United States are exclusively breastfed for the first 6 months of life. In 2019, the infants least likely to be exclusively breastfed at 6 months are African Americans (AA) (17.2%). Materials and Methods: A scoping review of the literature was undertaken by using Arksey and O'Malley's sixstage framework to determine key themes of AA women's experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 41 publications
2
28
0
1
Order By: Relevance
“…The incorporation of cross-cultural and mental health components into such programmes, if done correctly, could lead to a "socially sensitive" approach to breastfeeding (Leeming et al, 2013) which would entail "listening to women's voices" across diverse cultures (Ting and Panchanadeswaran, 2009). Such an approach could lead to greater equity in breastfeeding practices at a global level (Gyamfi et al, 2021;Vilar-Compte et al, 2021;North et al, 2022), leading to better health outcomes for both mothers and their children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of cross-cultural and mental health components into such programmes, if done correctly, could lead to a "socially sensitive" approach to breastfeeding (Leeming et al, 2013) which would entail "listening to women's voices" across diverse cultures (Ting and Panchanadeswaran, 2009). Such an approach could lead to greater equity in breastfeeding practices at a global level (Gyamfi et al, 2021;Vilar-Compte et al, 2021;North et al, 2022), leading to better health outcomes for both mothers and their children.…”
Section: Discussionmentioning
confidence: 99%
“…Those involved in providing breastfeeding support should ensure that unsupportive or hostile attitudes and beliefs are discarded, whether these arise from family members or from healthcare workers unfamiliar with the sensitive nature of this work (Sharma and Byrne, 2016;Pezley et al, 2022). Finally, it is essential that those seeking to provide help to breastfeeding mothers familiarize themselves with the unique social, cultural and economic contexts of women from specific communities, particularly if they face other forms of discrimination or marginalization (Gyamfi et al, 2021).…”
Section: Cultural Sensitivitymentioning
confidence: 99%
“…The outcome of this meta-ethnography underscores the relevance of social support as a key determinant of BF among AA women in the United States. 8 , 34 African American women in the United States may breastfeed if the reported BF social support needs are recognized and fully met. Provision of expressed BF social support needs will favorably contribute toward the achievement of the Healthy People's 2030 goal (42.4% 6 months of EBF target for all American infants) and World Health Organization's 6 months of EBF target of at least 50% by 2030.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant AA women in the United States, like many women, usually make their BF decisions in consultation with their family and peers based on several socioeconomic, health, political, cultural, and religious factors. [8][9][10] For instance, partners (fathers) who Breastfeeding Social Support Among African American Women obtained increased knowledge in lactation during an experimental study showed readiness to support maternal BF efforts. 9 In a related study, 10 most mothers (71%) reported the need for improvement in prenatal education and reinforcement of BF exclusivity through outpatient services.…”
mentioning
confidence: 99%
“…15 Low socioeconomic status increases exposure to factors known to increase a mother's risk of not meeting her lactation goals including living in disadvantaged and more segregated neighborhoods and household food insecurity. [16][17][18] Mothers who report food insecurity cease lactation earlier often due to concerns regarding milk quality and quantity. 19 Furthermore, education, a marker of socioeconomic status, is well known to be associated with improved lactation outcomes in mothers of both preterm and term infants likely due to increased job mobility and available funds to purchase pumps, lactation education, childcare, and assistance with household duties.…”
mentioning
confidence: 99%